Programma: 22-26 maart; 23&24 maart: Indiaas festival; 22,25-26 maart: Dance Theatre Cooperative met Mobile III; 25-26 maart: Abrakadabra (1978)
Programma: 22-26 maart; 23&24 maart: Indiaas festival; 22,25-26 maart: Dance Theatre Cooperative met Mobile III; 25-26 maart: Abrakadabra.